Experimental attempts of using modulated and unmodulated waves in low-frequency acoustic wave flame extinguishing technology - Wilk-Jakubowski, Jacek (Strojniški vestnik, 2024)
In practice, some undesired signals perceived as noise (because of the sound sensation) can effectively extinguish flames. This article provides information on the applicability of acoustic waves (a case of using sine waves and sine waves amplitude modulated by a square waveform) in low-frequency acoustic wave flame extinguishing technology based on experimental results obtained from a laboratory stand, which is a scientific novelty. The benefits of using deep neural networks for flame detection based on dedicated solutions developed through international cooperation are also recognized. In addition, the potential advantages of combining both technologies (use in fully automatic systems), limitations, open problems, and plans for further research are identified. The paper concludes that it is possible to extinguish flames as soon as they appear (firebreaks) and prevent large fires from breaking out. This feature may effectively reduce material losses and increase widespread safety.
Keywords: acoustic flame extinguishing; akustično gašenje plamena; deep neural networks; dušenje plamena; fire extinguisher; firefighting systems; flame suppression; gasilni sistemi; globoke nevronske mreže; protipožarne prepreke